(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Archibald “Archie” Cochrane is the brilliant creator of the evidence-based medicine (EBM). His book “Effectiveness and Efficiency: random reflections on health services” is one of the fundamental texts of Medicine today. For his influence on the progress of medicine, Cochrane may be considered one of the greater physicians of all time. He gave an exceptional boost to the improvement of medical practice worldwide. Cochrane’s vision of medicine and his great scientific achievements are still alive through the Cochrane Collaboration, an organization which provides valuable impulses to improving the quality of medical care. Also he was a great epidemiologist, very proud of his epidemiological work, and his life is interesting for adventurous events and extraordinary examples of righteousness and generosity.